Near wall treatment in turbulence model - Tan, Huat Yong (2008)
This work presents the extension of the Cabot’s Wall Model (CWM) originally developed for Large Eddy Simulation (LES), to the turbulence closure models. It allows the simulation to be conducted on relatively coarse grid, with the first off wall core grid point typically located in the log region instead of the viscous region for those cases using solely Low Reynolds Number (LRN) modeling.